Nonsuicidal self-injury among Chinese university students during the post-COVID-19 era: analysis of sex differences and the impact of gender role conflict - Xin, Moye; Petrovic, Julia; Yang, Chengxi; Zhang, Lijin; Yang, Xueyan (Frontiers in Psychology, 2024)
Background: Global centres of epidemic prevention and control have entered a new stage of normalization, namely, the "post-COVID-19 era" . During the post-COVID-19 era, which is characterized by the time period following that with the most serious medical consequences, the psychosocial consequences of the COVID-19 pandemic began to receive worldwide attention, especially the degree of psychological distress it caused. Aim: This study explored the differential impact of gender role conflict on Chinese university students' engagement in nonsuicidal self-injury (NSSI) as a function of biological sex following the global COVID-19 pandemic. Methods: Participants were 1600 university students in northwestern China (Mage = 21.3 years; 50.8% women) who completed online measures of demographic variables (including biological sex, gender role conflict, and NSSI engagement).Results: Women reported significantly more gender role conflicts than men did, while engagement in NSSI was significantly more prevalent among men than women.A total of 262 men reported engaging in at least one NSSI behaviour, resulting in a prevalence rate of 33.25%. In comparison, a total of 106 individuals reported engaging in at least one NSSI behaviour, resulting in a prevalence rate of 13.05% among women. Gender role conflict was found to significantly predict university students' NSSI engagement, regardless of biological sex.Conclusions: This is the first empirical study to identify sex differences in both gender role conflict and engagement in NSSI among university students in Northwestern China during the post-COVID-19 era. In addition, the present study is the first to demonstrate how gender role conflict predicts engagement in NSSI across sexes. These findings will inform the literature on gender role conflict and NSSI, particularly the close relationship between gender role conflict and engagement in NSSI among Chinese university students, and they emphasize the need for continued efforts to explore NSSI cross-culturally.